Network Meta-Analysis of Once Weekly Selinexor-Bortezomib-Dexamethasone in Previously Treated Multiple Myeloma - Michael Dolph; Gabriel Tremblay; Adrienne M Gilligan; Hoyee Leong (Journal of Health Economics and Outcomes Research, 2021)
# Background Despite the availability of new treatments, multiple myeloma (MM) is an incurable cancer with nearly all patients relapsing and undergoing multiple lines of treatment. Performing head-to-head comparisons of all treatment options is not feasible. Thus, network meta-analyses play an important role in allowing health-care decision makers to compare the effectiveness of treatment options.